Quantitative PCR for HTLV‐1 provirus in adult T‐cell leukemia/lymphoma using paraffin tumor sections. Issue 11 (27th September 2016) - Kato, Junki; Masaki, Ayako; Fujii, Keiichiro; Takino, Hisashi; Murase, Takayuki; Yonekura, Kentaro; Utsunomiya, Atae; Ishida, Takashi; Iida, Shinsuke; Inagaki, Hiroshi
Abstract : Detection of HTLV‐1 provirus using paraffin tumor sections may assist the diagnosis of adult T‐cell leukemia/lymphoma (ATLL). For the detection, non‐quantitative PCR assay has been reported, but its usefulness and limitations remain unclear. To our knowledge, quantitative PCR assay using paraffin tumor sections has not been reported. Using paraffin sections from ATLLs and non‐ATLL T‐cell lymphomas, we first performed non‐quantitative PCR for HTLV‐1 provirus. Next, we determined tumor ratios and carried out quantitative PCR to obtain provirus copy numbers. The results were analyzed with a simple regression model and a novel criterion, cut‐off using 95 % rejection limits. Our quantitative PCR assay showed an excellent association between tumor ratios and the copy numbers ( r = 0.89, P < 0.0001). The 95 % rejection limits provided a statistical basis for the range for the determination of HTLV‐1 involvement. Its application suggested that results of non‐quantitative PCR assay should be interpreted very carefully and that our quantitative PCR assay is useful to estimate the status of HTLV‐1 involvement in the tumor cases. In conclusion, our quantitative PCR assay using paraffin tumor sections may be useful for the screening of ATLL cases, especially in HTLV‐1 non‐endemic areas where easy access to serological testing for HTLV‐1 infection is limited.